2002
DOI: 10.1200/jco.2002.09.112
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Adjuvant Trial of Tamoxifen and Goserelin Versus Cyclophosphamide, Methotrexate, and Fluorouracil: Evidence for the Superiority of Treatment With Endocrine Blockade in Premenopausal Patients With Hormone-Responsive Breast Cancer—Austrian Breast and Colorectal Cancer Study Group Trial 5

Abstract: Overall, our data suggest that the goserelin-tamoxifen combination is significantly more effective than CMF in the adjuvant treatment of premenopausal patients with stage I and II breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(135 citation statements)
references
References 24 publications
6
120
0
9
Order By: Relevance
“…22 In addition, the results from several large, randomized trials recently have confirmed the role of Gn-RH analogues in the adjuvant treatment of early breast carcinoma either as monotherapy 23 or in combination with tamoxifen and/or chemotherapy. 24,25 In particular, the Zoladex Early Breast Cancer Research Association trial, which compared the efficacy and tolerability of goserelin with that of CMF, after a median follow-up of 7.3 years, showed equivalence between goserelin and CMF for disease-free survival and overall survival in patients with ER positive disease and demonstrated the superiority of CMF for both disease-free survival and overall survival compared with goserelin in patients who had ER-negative tumors. 25 Because of the presence of several heterogeneous cell populations in the same breast carcinoma, theoretically, neither ovarian ablation nor chemotherapy is capable of eradicating all cell clones that compose a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, the results from several large, randomized trials recently have confirmed the role of Gn-RH analogues in the adjuvant treatment of early breast carcinoma either as monotherapy 23 or in combination with tamoxifen and/or chemotherapy. 24,25 In particular, the Zoladex Early Breast Cancer Research Association trial, which compared the efficacy and tolerability of goserelin with that of CMF, after a median follow-up of 7.3 years, showed equivalence between goserelin and CMF for disease-free survival and overall survival in patients with ER positive disease and demonstrated the superiority of CMF for both disease-free survival and overall survival compared with goserelin in patients who had ER-negative tumors. 25 Because of the presence of several heterogeneous cell populations in the same breast carcinoma, theoretically, neither ovarian ablation nor chemotherapy is capable of eradicating all cell clones that compose a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…All patients had participated in either ABCSG Trial 05 or ABCSG Trial 06 and have received tamoxifen as part of their adjuvant treatment. Inclusion criteria and the main clinical results of both studies have been reported previously (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…Ovarian suppression has been under investigation in place of or in addition to adjuvant chemotherapy for young patients with newly diagnosed hormone-sensitive, early stage breast cancer [52][53][54]. In a large study comparing Sonmezer,Oktay 425 www.TheOncologist.com the efficacy and tolerability of monthly goserelin treatment for 2 years (n = 817) with CMF (n = 823), goserelin produced a similar DFS to that seen with CMF in estrogen receptor-positive patients after a median follow-up of 6 years [55].…”
Section: Use Of Nongonadotoxic Ovarian Suppression Regimens As Adjuvamentioning
confidence: 99%